Production and nutrition of maize (Zea maize) and millet (Pennisetum glaucum) with the application of porcine biofertilizer - Silva Moreira, Elwira Daphinn; Fernandes, L. A.; Alonso, Jatnel; Colen, F.; Roberto Cruz, L. (Cuban Journal of Agricultural Science, 2017)
To study the production and nutrition of corn and millet, fertilized with porcine biofertilizer, two experiments were established (one for each species) in a random block design with four replications and six treatments. These consisted of five doses of porcine biofertilizers, to offer 0, 50, 100, 150 and 200 kg ha-1 of P2O5, and an additional treatment with complete formula 4-14-8, in which was offered 79.99 kg ha-1 of P2O5.In the total fresh matter yields influenced the biofertilizers doses. The highest values (55.81 and 41.34 t ha-1) were reached with mineral fertilization, and did not differ from those obtained with the dose of 150 kg ha-1 of P2O5 (55.05 and 38.71 t ha-1) for millet and maize, respectively. The foliar nutrient content of crops was higher and similar with mineral fertilization and the higher doses of biofertilizers. It is concluded that the porcine biofertilizer, in the dose of 150 kg ha-1 of P2O5, can substitute the application of mineral fertilization in both species, and also constitute a source of micronutrients and macronutrients. Key words: grasses, organic fertilization, wastes, yield, mineral composition